Content Delivery Networks integrated with Software Defined Networks - Kopp, Samuel; Hernandez, Michael Prieto; Chigami, Lucas Takeshi; Silveira, Regina Melo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
The rise of Software-Defined Networking afforded a new cycle in research of Content Distribution Networks. Among this, many studies have investigated the approach of InformationCentric Networking. However, as already identified, this model has several limitations regarding their application in the context with global reach, i.e., on the Internet. In order to address this problem, this paper presents an architecture that integrates the CDNs and SDNs. Thus, It is proposed the use of a network abstraction layer that provides network services to intermediate the CDN service and the network’s infrastructure. The results obtained preliminarily, demonstrated that the proposed architecture allows you to apply traffic engineering mechanisms implemented in SDN to optimize the distribution of content through the CDN. Finally, we advocate that the proposed solution allows optimizing the distribution of content using SDN on the Internet, that is, even in contexts in which the CDN is operated by a different administrative entity that operates the SDN.